The Impact of Digital Quality Management on Achieving Organizational Loyalty: An Exploratory Study in the Iraqi Tourism Authority - Ryam Abdul-Wahab Ahmed (Academia Open, 2026)
General Background: The digital revolution has transformed organizational work environments and encouraged the adoption of digital approaches in management systems, including quality management practices. Specific Background: In tourism organizations, digital quality management represents an administrative approach that integrates digital technologies to manage services and operational processes while supporting organizational performance and employee commitment. Knowledge Gap: Despite the growing relevance of digital management practices, many institutions within the Iraqi tourism sector continue to rely on traditional administrative frameworks, which contribute to routine bureaucratic procedures and may weaken organizational loyalty among employees. Aims: This study aims to examine the relationship between digital quality management and organizational loyalty within the Iraqi Tourism Authority. Results: Using a descriptive analytical approach and questionnaire data collected from 100 managers across different administrative levels, the results indicate a statistically significant positive relationship between digital quality management and organizational loyalty. Structural Equation Modeling revealed a standardized path coefficient of 0.71, showing that digital quality management explains approximately 51% of the variation in organizational loyalty. Among its dimensions, data security recorded the highest mean score, while continuous loyalty ranked highest among loyalty dimensions. Novelty: The study provides empirical evidence on the relationship between digital quality management dimensions user experience, data security, responsiveness, and integration and innovation and organizational loyalty within a public tourism authority context. Implications: The findings highlight the need for tourism institutions to adopt modern digital quality management practices and foster an organizational culture that supports loyalty, innovation, and improved perception of the tourism authority’s role in economic and social development. Highlights: • Data Security Recorded the Highest Mean Among Digital Quality Dimensions Within the Tourism Authority.• Continuous Commitment Ranked First Among Loyalty Components in the Surveyed Managers.• Structural Equation Modeling Revealed That Digital Quality Practices Explain Over Half of Loyalty Variance. Keywords: Digital Quality Management, Organizational Loyalty, Iraqi Tourism Authority, Tourism Management, Structural Equation Modeling